O processo de formação do assistente social: desafio permanente - Frois, Eliana Aparecida Gonçalez Albonette (2009)
The current thesis has the social worker majoring process: a permanent challenge as a theme whose aim was to scrutinize the academician acting in this procedure. In order to make it happen, a investigative path has been ridden on Education and social service altogether. In this theses I try to explore the limitations and possibilities as to critical and ethical social workers are majored, highlighting academician role in the information process, taking into account the ethical-political project and its ethical code as a craft as well. One of the major promises in which the research has its heart on, is a acknowledgement that the social worker as a social services majoring academician needs some knowledge from teaching to exercise this practice, for only professional exercise doesn t make them eligible for such. To perform such research it was necessary to study a graphic learning process for the Social Services graduates in its completion comprehending the ground rules and peculiarities of this process. For such, it has been searched as a Universe of research the Universidade Estadual de Londrina, PR, the social work majoring course. The aim of researching the academician professional exercise in graduation level in social services from UEL/ PR, had been reaching and yet, knowing the requirements which are made for those professionals, concerning the determiners and peculiarities of this kind work detect as the teaching/learning process has been happening to the Social services majoring undergraduates. In closing the thesis, considerations are composed retrieving the limitations and mostly the possibilities held in the concrete reality on the daily basis, in school vicinity, where soon-to-be social workers are majored, highlighting some purposes in a sense of collaborating with such category. Directing enabling actions to enhance the social worker majoring as a permanent challenge